Knowledge, Adoption and Constraints of Soil Health Card based Fertilizer Application in Ratlam District, M.P. - Ghaswa, Ramdhan; Tripaty, Sarvesh; Sharma, Barkha (Indian Journal of Extension Education, 2019)
Since inception of soil health card programme during 2015-16 in order to increase agricultural production and sustain soil health, a large number of soil health cards have been distributed to the farmers. In order to assess the knowledge, adoption and constraints of soil health card, the present study was carried out. The farmers who were issued soil health card were comparatively more aware about various soil health card aspects like major nutrients (N, P & K), soil pH, soil EC and micronutrients as compared to farmers without soil health card. Data shows that maximum number of respondents had medium knowledge score that is 56.95 per cent followed by respondents with low knowledge score (23.61%) and only 19.44 per cent respondents had high knowledge score about soil health card. Major constraints faced by the farmers in adoption according to soil health card were difficulty in having knowledge about the importance of micronutrients, the prices of fertilizers being too high and non-availability of organic manure.
Keywords: Adoption; Constraints; Farmer’s; Knowledge; Soil health card